71.7k views
2 votes
If (-1, y) lies on the graph of y = 3^x+1, then y =

User Vreyespue
by
5.1k points

2 Answers

1 vote

Answer:

y = 4/3

Explanation:

y = 3^x+1

Substitute -1 for x.

y = 3^(-1)+1

y = 1/3 + 1

y = 1/3 + 3/3

y = 4/3

User Jeffrey Basurto
by
5.4k points
2 votes

Answer:

If this was your equation
y=3^x+1 then the answer is 4/3.

If this was your equation
y=3^(x+1) then the answer is 1.

Explanation:

It is basically asking us to replace x with -1 and find y.

If
y=3^x+1 and we plug in -1 for x, we get
y=3^x+1=3^(-1)+1=(1)/(3)+1=(4)/(3) .

If
y=3^(x+1) and we plug in -1 for x, we get
y=3^(x+1)=3^(-1+1)=3^0=1.

User Donkarnash
by
5.4k points